Teachers' perceptions of successful transition to school for children with and without Downs Syndrome in the UAE and England. Issue 7 (3rd October 2021) - Atkinson, Susan J.; Takriti, Rachel A.; Elhoweris, Hala
ABSTRACT: The experience of transition into school has been shown to correlate with later school outcomes, with a successful experience resulting in later positive academic and social outcomes. Children with Special Educational Needs (SEN) face more challenging transitions. Teacher attitudes and expectations of children with SEN play a key role in determining the quality of the transition. Early Years Foundation Stage teachers were recruited from the UK and from the UAE. They completed a questionnaire twice, rating the importance of factors in ensuring a successful transition to school for children with no SEN and with Downs Syndrome. Significant differences in the rating of factors were found for the two groups of children. Between-country differences were significant for Knowledge and for Academic factors. The implications of differences in expectations cross-culturally and for children with SEN are discussed.